2022
DOI: 10.1111/aej.12652
|View full text |Cite
|
Sign up to set email alerts
|

Working length determination in primary teeth pulpectomy: A systematic review and meta‐analysis

Abstract: The present meta‐analysis aimed to describe the methods to determine the working length in primary teeth pulpectomy, also evaluating and comparing their reliability. A systematic review was performed following the PRISMA Statement. The electronic search was conducted on PubMed, Scopus, Cochrane Library and Web of Science. After the screening protocol, a number of 14 studies were included in the qualitative analysis, while seven were included in the quantitative one. The mean working length determined by the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…17 With regard to the determination of the initial working length, a study has compared different apical locators with other methods, concluding that the methods achieve similar results in determining working length in primary teeth and apical locators can be used as a safe alternative. 19 Although the literature suggests the use of this method, most faculty members recommended measurement through the initial radiograph with a millimetre ruler. A possible reason for the non-use of apical locators is that faculty members may believe that these tools are inadequate due to root resorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 With regard to the determination of the initial working length, a study has compared different apical locators with other methods, concluding that the methods achieve similar results in determining working length in primary teeth and apical locators can be used as a safe alternative. 19 Although the literature suggests the use of this method, most faculty members recommended measurement through the initial radiograph with a millimetre ruler. A possible reason for the non-use of apical locators is that faculty members may believe that these tools are inadequate due to root resorption.…”
Section: Discussionmentioning
confidence: 99%
“…The literature, however, supports the use of electronic apex locators in primary teeth, regardless of the root resorption stage. 19 Another potential reason is a lack of mastery over clinical techniques or concerns about cost. It was not the aim of the present study to explore the underlying reasons, and further studies should be conducted to address this subject.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that factors such as metallic restorations, excess electrolytes, blood or exudate in the canal, caries, saliva, canal instruments in another canal, debris accumulation in the canal, and calcifications can negatively affect WL measurement [10]. Various studies have shown that pulp vitality, the presence of electrolyte in the canal, the degree of resorption, canal width, the diameter of the canal instrument, and differences in experience among practitioners can negatively affect the success of EALs [11][12][13].…”
Section: Introductionmentioning
confidence: 99%